Snowy : the making of modern Australia - Collis, Brad, 1955- (Melbourne, VIC : Coretext Books, 2015)
The Snowy Mountains Scheme changed Australia forever. A country founded on stolid British stock almost overnight became one of the world’s great pancultures. Tens of thousands of workers from more than 30 lands poured into what was the undisturbed pastoral realm of the high country stockman, the southern Outback. As they drilled and tunnelled into the mountains their energy and skills gave the country a mighty push into the vanguard of the twentieth century. The vibrant interaction of their many diverse cultures and the scale of the project in terms of technology made the Scheme an engineering wonder. In this edition, two new chapters have been added to cover this fascinating period.
Includes index.
Originally published in 1990 by Hodder & Stoughton.
Keywords: Snowy Mountains Hydro-Electric Authority -- History; Snowy Mountains Hydro-Electric Scheme -- History; Water resources development -- New South Wales -- Snowy Mountains -- History; Hydroelectric power plants -- New South Wales -- Snowy Mountains -- History; Snowy Mountains Region (N.S.W.) -- History; Australian